Cloning and characterization of terpene synthase genes from Taiwan cherry - Huang, Kuan-Feng; Wen, Chi-Hsiang; Lee, Yi-Ru; Chu, Fang-Hua (Tree genetics & genomes, 2019)
Prunus campanulata Maxim. also known as Taiwan cherry is a broadleaf tree native to Taiwan and is highly valued as an ornamental tree. Terpenoids are one of the most important sources of plant secondary metabolites with many functions such as attracting pollinators, defending against herbivores, and acting as anti-bacterial agents. Here, the terpene synthases (TPSs) that produce small and volatile monoterpenes or sesquiterpenes were focused. Using next-generation sequencing (NGS) technology, we obtained nine full-length cDNAs from P. campanulata which were predicted to encode TPSs. The predicted proteins possessed typical characteristics of TPSs, such as the highly conserved RRX 8 W and DDXXD motifs. To identify the functions of these TPSs, the recombinant proteins were reacted with the substrate to produce corresponding monoterpenes and sesquiterpenes. Analysis results revealed that the eight TPSs produced their corresponding major monoterpenes and sesquiterpenes, except for one TPS gene that lacks a part of the N-terminus sequence. MeJA treatment (10 mM) resulted in differential expression of these nine TPSs, suggesting that they may have different regulation mechanisms with different functions in plants.